Evaluasi Teknis Geometri Peledakan untuk Mendapatkan Fragmentasi dan Identifikasi Tingkat Keseragaman Batuan Hasil Peledakan yang Ideal di PT. Allied Indo Coal Jaya, Kecamatan Talawi, Kota Sawahlunto - Aulia Defriansyah; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT.Allied Indo Coal Jaya is a coal company located in Talawi District, Sawahlunto City. This company conducted the exploration by open pit and underground mining. In open pit mining, before the start of coal mining, overburden demolition is carried out first with blasting activities. Actual blasting geometry with explosive hole diameter 3inch, 2,873 m spacing, burden 2,8596 m, explosive hole depth 5,633 m, subdrilling 0,183 m, column length 2,979 m, stemming 2,655 m, level height 5,45 m and PF value 0,098 kg/m3. Percentage of rock fragmentation resulting from blasting on actual geometry using split desktop with fraction size ≥50 cm which is 35,17%, and the level of rock uniformity obtained is 2. Therefore, the author tries to propose blasting geometry so that the resulting fragmentation can meet the policies that have been made and the non-uniformity of the rock results can be better. The proposed geometry uses the ICI-Explosive formula with a 2,7 m space, 2,1 m burden, 5,4 m level height, 4,1 m column length, 1,9 m stemming, 0,6 m subdrilling, explosive hole depth 5 meters, and PF 0,20 kg/m3. Based on the geometry design, the proposed percentage of rock fragmentation results from the Kuz-Ram method with a fraction size of ≥50 cm which is 27,35%, while the percentage of rock fragmentation resulting from blasting uses split desktops with fraction ≥50 cm, 19,61%, and uniformity rock obtained is 1,23. Keywords:  Overburden, Blasting, Fragmentation, Kuz-Ram Method, Split Desktop.